ANALISIS EFISIENSI TEKNIS USAHATANI PENANGKARAN BENIH PADI POLA KEMITRAAN DI KABUPATEN SUBANG: PENDEKATAN STOCHASTIC FRONTIER ANALYSIS - Amalia Ulpah; Netti Tinaprilla; Lukman M Baga2 (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2018)
Analysis of Technical Efficiency From Rice Seed Breeding Farming with Partnership in Subang Regency: Stochastic Frontier Analysis Approach. Rice seed breeding farms is an alternative for farmers in increasing their income. But sometimes the lack of capital and knowledge is an obstacle for breeder farmers, which has an impact on low productivity. The partnership between farmers and partner companies can be a solution for improving technical production efficiency so that productivity can increase. This study aims to determine the level of technical efficiency of rice seed production through a partnership schme in Subang regency, West Java and study the factors that influence the efficiency of rice seed production. Fifty respondents in Tolangohula Sub district, Subang District, Gorontalo Province were selected by accidental sampling method Samples taken in this research are 50 breeder farmers, consisting of farmers who are partners and who do not partner. Stochastic Frontier Analysis (SFA) was employed to estimate technical efficiency and to find the factors that affected the efficiency of rice seed breeding farming. Results of the analysis showed that the farming of all respondent farmers was technically efficient with an average efficiency index of 0.92. Technical efficiency of partner farmers is higher than non-partner farmers, average efficiency of partner farmers is 0.93 while the average efficiency of non-partner farmers is 0.90, but the partnership did not significantly affect the efficiency. Factors that influenced the technical efficiency were age and farming experience. Technical efficiency can be increased if farming is done by young farmers and with intensive training and mentoring, because its can improve farmers’ experience and farmers’ knowledge.ABSTRAKUsahatani penangkaran benih padi menjadi salah satu alternatif bagi petani dalam meningkatkan pendapatannya. Namun terkadang ketersediaan modal dan pengetahuan menjadi hambatan bagi petani penangkar yang berdampak pada rendahnya produktivitas. Pola kemitraan antara petani dan perusahaan mitra dapat menjadi solusi memperbaiki efisiensi teknis produksi agar produktivitas meningkat. Penelitian ini bertujuan untuk menganalisis tingkat efisiensi teknis produksi benih padi melalui pola kemitraan dan faktor-faktor yang mempengaruhi efisiensi produksi benih padi di Kabupaten Subang, Propinsi Jawa Barat tersebut. Total sampel dalam penelitian sebanyak 50 petani penangkar, terdiri dari petani mitra dan petani non mitra. Analisis efisiensi dan faktor-faktor menggunakan pendekatan Stochastic Frontier Analysis (SFA). Hasil analisis menunjukkan bahwa usahatani untuk seluruh petani responden telah efisien dengan tingkat efisiensi rata-rata sebesar 0,92. Efisiensi petani dengan pola kemitraan relatif lebih tinggi dibandingkan dengan petani non mitra (efisiensi petani mitra adalah 0,93 sedangkan petani non mitra adalah 0,90), namun kemitraan tidak berpengaruh signifikan terhadap peningkatan efisiensi teknis. Pola kemitraan yang berjalan tidak sempurna dapat mempengaruhi efisiensi teknis. Faktor yang berpengaruh nyata terhadap efisiensi teknis adalah usia petani dan pengalaman berusahatani. Efisiensi teknis dapat meningkat apabila usahatani dikerjakan oleh petani-petani usia produktif diikuti dengan pelatihan dan pendampingan yang intensif, karena pelatihan dan pendampingan mampu meningkatkan pengalaman dan wawasan petani.